The Relationship between the Intensity of Premenstrual Syndrome Symptoms and Marital Satisfaction among the Couples of Kerman City - Faramarz Shaahmadi; Ehsan Movahed; Sarallah Shojaei; Morad Ali Zareipour; Behrouz Lotfi mine blagh; Mahboubeh Ameri; Saiedeh Sadeghi (Journal of Research Development in Nursing and Midwifery, 2018)
Introduction: Premenstrual syndrome as a periodic event that social adjustment and interpersonal relationships can be difficult. Regarding the prevalence of premenstrual syndrome and the harmful effect of severity of symptoms on marital satisfaction, The aim of this study was to determine the relationship between severity of symptoms of premenstrual syndrome and marital satisfaction among couples in Kerman city in 2016. Methods: This cross-sectional study that randomized 240 young couples who referred to health centers in Kerman were selected in the second 6 months of 2016. The instrument used a standard questionnaire screening premenstrual symptoms, a standard questionnaire Index Of Marital Satisfaction for the satisfaction of couples. The investigators have assured that all information obtained will remain confidential Data were analyzed by SPSS 20 software using independent t-test, one-way ANOVA, correlation coefficient and frequency distribution tables. Results: The mean age of men and women respectively was equal to 35.5 ± 8.2 to 32.4 ± 7.6 . The mean and standard deviation of marital satisfaction score of women and men were (114.97 ± 23.27) and (125.25  ± 26.17 ) respectively There was a significant relationship between the satisfaction of men and women in relation to premenstrual syndrome (p=0/001).Pearson correlation showed an inverse relationship between the symptoms of premenstrual syndrome and couples' satisfaction. (r=-0.138 , P=0.002).. Conclusion: With increasing severity of premenstrual syndrome in women, marital satisfaction decreases among couples.. so it is recommendate that women and men receive the necessary knowledge about to control the symptoms of premenstrual syndrome. Keywords: Marital Relationship, couples، premenstrual syndrome